Saturday, 16 JUNE 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.1983
|View full text |Cite
|
Sign up to set email alerts
|

SAT0218 Efficacy and safety of baricitinib in mtx-ir patients with rheumatoid arthritis: 52 week results from a phase 3 study (RA-BALANCE)

Abstract: Background:Baricitinib (BARI) is an oral selective inhibitor of Janus kinase 1 (JAK1) and JAK2. In the EU and some other countries, baricitinib has been approved for the treatment of moderately to severely active rheumatoid arthritis (RA) in adult patients. This abstract reports efficacy and safety results from a phase 3, double-blinded, 52-week study (RA-BALANCE) that enrolled patients (pts) in China, Argentina and Brazil (NCT02265705).Objectives:To assess the efficacy and safety of BARI vs placebo (PBO) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
2
4
0
1
Order By: Relevance
“…Here, we report the first integrated safety profile of baricitinib in EA patients, with moderate‐to‐severely active RA for 1294 PY of exposure (median 1.9 years, maximum 3.5 years). The results from the current analysis are consistent with previously published integrated safety reported in a Japanese population and also with RA‐BALANCE (NCT02265705) study conducted primarily in a Chinese population with moderate‐to‐severely active RA . Recently, the RA‐BALANCE study demonstrated rapid and durable efficacy results with baricitinib 4 mg once daily compared to placebo in patients with inadequate response to MTX.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here, we report the first integrated safety profile of baricitinib in EA patients, with moderate‐to‐severely active RA for 1294 PY of exposure (median 1.9 years, maximum 3.5 years). The results from the current analysis are consistent with previously published integrated safety reported in a Japanese population and also with RA‐BALANCE (NCT02265705) study conducted primarily in a Chinese population with moderate‐to‐severely active RA . Recently, the RA‐BALANCE study demonstrated rapid and durable efficacy results with baricitinib 4 mg once daily compared to placebo in patients with inadequate response to MTX.…”
Section: Discussionsupporting
confidence: 89%
“…The occurrence of clinically important safety outcomes, including serious infections, was similar between both groups. No unexpected safety signals were observed . This analysis is further confirmed by the data from LTE study with a broader EA population.…”
Section: Discussionsupporting
confidence: 78%
“…All approved JAK inhibitors were more efficacious than csDMARDs with 95% probability. At both time points, upadacitinib 15 mg QD monotherapy and in combination with csDMARD consistently demonstrated numerically higher responses in terms of ACR 20/50/70 and DAS28-CRP remission among patients with csDMARD-IR RA compared with other JAK inhibitors [39].…”
Section: Discussionmentioning
confidence: 90%
“…Thirdly, inclusion of trials allowing for lower background dose of methotrexate (MTX) in the network might also constitute another source of heterogeneity, the impact of which on treatment response has not been reported. We specifically refer here to the inclusion of RA-BALANCE [ 4 ] and SELECT-SUNRISE [ 5 ], in some of the networks, where the dosage of MTX was much lower than that reported in other included trials in the networks. Trials including Asians-Japanese patients with lower MTX dose should have been excluded in a sensitivity analysis and impact on results compared.…”
Section: Lettermentioning
confidence: 99%